Jaw tumor in recurrent primary hyperparathyroidism: A case report. (2018) - Amini Nezhad, Farzaneh; Payab, Moloud; Nayebandi, Sara; Hasani-Ranjbar, Shirin
Highlights: Brown tumor may present as uni/multilocular osteolytic lesions with bone expansion, bone pain or pathologic fracture in primary, secondary and tertiary hyperparathyroidism. Recently, such presentation is rare because of early detection before symptomatic bone lesions appear due to improved blood screening techniques. The reported case is a 65-year-old female presented with recurrent hyperparathyroidism and a tumoral mass in her jaw. Although recurrent Hypercalcemia with high serum PTH level, jaw tumor, and bilateral parathyroid adenomas in99mTc-MIBI parathyroid scintigraphy suggesting HPT-JT, her old age, lack of similar familial history, absence of nonendocrine malignancy as well as evidence of malignancy in the patient's parathyroid pathology, this diagnosis was not supported. Abstract: Background: Brown tumor may present as uni/multilocular osteolytic lesions with bone expansion, bone pain or pathologic fracture in primary, secondary and tertiary hyperparathyroidism. However, recently, such presentation is rare due to early detection using blood screening techniques before symptomatic bone lesions appear. Case Report: A 65-year-old woman was admitted to our hospital with generalized bone pain and a progressive painless mass in her jaw appeared since 6 months ago. She had a history of two times parathyroidectomy. In recent hospitalization, she presented with the complaint of weakness, bone pain and a progressive swelling in her jaw. Laboratory analysis showed a hypercalcemia and plasma PTH of 398 pg/ml. Dual energy X-ray (DXA) showed osteoporosis at the neck of hip and lumbar spine. The neck MRI revealed an 11 * 6 mm soft tissue nodule posterior to left thyroid lobe and a 20*18 mm T2 hypersignal, T1hyposignal nodule at right thyroid lobe. The SPECT-CT scintigraphy with 99mTc-MIBI was suggestive of bilateral parathyroid adenomas and/or parathyroid hyperplasia and showed a MIBI- avid lytic lesion in the mandible. Surgical management was performed. After removing the adenoma the PTH marked a decrease from the initial value to 57 pg/ml. The histological examination revealed the thyroid tissue with MNG and a left parathyroid adenoma. Follow-up after surgery revealed normal blood calcium and urine calcium levels with no increase. PTH levels also did not increase. The patient was treated with calcium and vitamin D supplements and the jaw mass decreased gradually. Conclusions: Primary or secondary HPT may be recognized by the presence of an osteolytic lesion with giant cells, a condition referred as brown tumor. Consideration should be made that non-specificity of hypercalcemia symptoms can also be a bone tumor including jaw lesion as a manifestation of hyperparathyroidism.